Determinants and economic burden of HIV/AIDS in Iran: a prospective study - Tahmineh Reshadat-Hajiabad; Alireza Khajavi; Ali Mohammad Hosseinpour; Amin Bojdy; Amir Hashemi-Meshkini; Mehdi Varmaghani (BMC, 2023)
Abstract Background Since the start of the AIDS outbreak, the human immunodeficiency virus (HIV) has infected about 84.2 million people, and approximately 40.1 million people have died due to AIDS-related diseases. So, this study aims to provide a comprehensive population-based description of patient costs and the economic burden of HIV/AIDS in Iran. Methods The study population of this cross-sectional cost-of-illness study consisted of HIV-infected patients who were receiving services in Mashhad and were under the supervision of BIDCC. There are four BIDCC centers in Mashhad, we considered all patients referred to these centers. Costs data were evaluated from a social perspective with a bottom-up approach and as a prevalence based. The data from 157 individuals were included in the study. For collecting data on direct and indirect costs belonging to patients and their families, a questionnaire was developed. Also, the Demographic characteristic of participants and the stage of the disease and Transmission category were analyzed. Results In this study, 57.32 of the subjects were Male. The majority of participants in this study were in the age group 30-59 years (n = 124,78.98%). Based on where the patients live, the majority of patients have lived in the urban region (n = 144, 91.72%). The most common way to transmit this disease is through unprotected sex (30.57%) and then Infected spouse (28.03%), and then injecting drugs (21.02%). The highest cost of this disease is attributed to medicine (10339.32 $ for 6 months), after medicine, the cost of tests was 9101.22 $. Conclusion It seems that to reduce costs for patients with disease HIV/AIDS, the focus should be on diagnostic tests and care. Early diagnosis and rapid initiation of antiviral treatments can be effective in preventing serious and debilitating diseases.